Teaching for the Flourishing Future: Educational Policy and Political Education following Chile's Democratic Transition - Henderson, Rita Isabel (Anthropologica, 2013)
In 2011, a Chilean student strike rattled the coun try's political establishment in a way that no union has managed to do since the 1990 democratic transition. On-the-ground conse quences of macro-changes to public education in recent decades frame pervasive disappointment in forms of political participa tion accorded to citizens. I explore here student, teacher and parent experiences with underfunded rural schools as a means of uncovering important temporal and affective politics struc turing formal schooling in Chile today. It is no accident that the state's progressive retraction from funding public edu cation coincides with growing interest among multinational investors to sponsor children in need.